Bonjour,
1)
A = 2 (3x + 5) + 4 (2x + 1)
A = 6x + 10 + 8x + 4
A = 6x + 8x + 10 + 4
A = 14x + 14
B = 3 (x - 7) + 5 (2x - 4)
B = 3x - 21 + 10x - 20
B = 3x + 10x - 21 - 20
B = 13x - 41
C = x (3x + 2) + 3 (4x + 4) - 3x (2x + 7)
C = 3x² + 2x + 12x + 12 - 6x² - 21x
C = 3x² - 6x² + 2x + 12x - 21x + 12
C = - 3x² - 7x + 12
D = (4x + 3) (3x + 7)
D = 12x² + 28x + 9x + 21
D = 12x² + 37x + 21
E = (3x - 1) (x + 9)
E = 3x² + 37x - x - 9
E = 3x² + 36x - 9
F = (x - 8) (4x - 3)
F = 4x² - 3x - 32x + 24
F = 4x² - 35x + 24
G = (3x - 2) (3x + 2)
G = 9x² + 6x - 6x - 4
G = 9x² - 4
Pour le 2) tu fais un autre post merci.